Oedipus the King - Sophocles (Greek tragedy in new translations., 1988)
Based on the conviction that only translators who write poetry themselves can properly recreate the celebrated and timeless tragedies of Aeschylus, Sophocles, and Euripides, theGreek Tragedy in New Translationsseries offers new translations that go beyond the literal meaning of the Greek in order to evoke the sense of poetry evident in the originals. Under the editorship of Peter Burian and Alan Shaprio, each volume includes a critical introduction, commentary on difficult passages, ample stage directions, and a glossary of the mythical names and geographical references encountered in the dialogue. Sophocles'Oedipus the Kingpaves the way as the first in the series to appear in paperback. In this highly-acclaimed translation of the greatest of all Greek tragedies, Stephen Berg--the well-known poet--and Diskin Clay--the distinguished classicist--combine their talents to offer the contemporary reader a dazzling version of Sophocles' timeless work. Emphasizing the intensity of the spoken language, they capture the unrelenting power of Sophoclean drama. No other English translation conveys the same terrifying emotional level, especially in the choral odes, the forceful descriptions of Jokasta's death, the blinding of Oedipus, and the final scene of desolation. Berg and Clay's translation--now available for the first time in paperback--both adheres strictly to the original meaning of the play and breathes new life into its language.